Transcriptional Regulation of the rsbV Promoter Controlling Stress Responses to Ethanol, Carbon Limitation, and Phosphorous Limitation in Bacillus subtilis - Soo-Keun Choi; Milton H. Saier (International Journal of Microbiology)
The σB-dependent promoter in front of the rsbV gene of Bacillus subtilis is induced ∼5-fold in response to (1) the addition of 4% ethanol, (2) carbon starvation, and (3) phosphorous starvation. Binding sites for the global carbon and nitrogen regulators, CcpA and TnrA, were mutated, and the consequences of their loss and that of CcpA or TnrA were studied using rsbV-lacZ fusions. These responses proved to be dependent on CcpA, TnrA, and their putative binding sites upstream of the promoter. Induction in response to glucose limitation was largely abolished by loss of CcpA or the upstream region, while induction in response to phosphorous limitation was largely abolished only by the upstream mutations. The results suggest that CcpA directly influences the carbon starvation response and that both proteins exert indirect effects on all three stress responses. The integrity of the DNA sequence is important for all three responses.